A new viscoelastic artificial boundary with improved numerical stability in explicit calculation of wave propagation problems in infinite domains. (May 2022) - Bao, Xin; Liu, Jing-Bo; Li, Shu-Tao; Wang, Fei
Abstract: The viscoelastic artificial boundary is currently a practical numerical method for addressing the wave propagation problem in infinite domain. When applying this method in explicit dynamic calculations, however, the stability conditions of the boundary area are more stringent than those of the internal domain, leading to smaller critical integral time increments and heavy computational workloads. In this study, the stability conditions of the viscoelastic artificial boundary and their influencing factors in an explicit integral algorithm are analyzed. On that basis, a stability improvement method by introducing added mass to the artificial boundary is proposed. Then through a parametric analysis, the recommended values of the introduced added mass are presented. After adopting these recommended values, the stability conditions of the artificial boundaries get loosed, and the stability of the overall numerical system is controlled by the internal area. Therefore the stability condition of the internal domain can be used to estimate the critical time increment in the explicit calculation. Numerical examples show that the improved viscoelastic artificial boundary proposed in this study can maintain the accuracy of the original method while significantly improving the calculation efficiency, thus offering strong practicability.